Kritis Sejak Awal: Penguatan Kemampuan Berpikir Kritis Dan Liberasi Digital Bagi Mahasiswa Baru Fisip UPNVJ - Mansur Juned; Abdullah Arif; Mohamad Hery Saripudin; Syahrul Salam; Aan Setiadarma (AMMA : Jurnal Pengabdian Masyarakat, 2026)
The democratization of information through digital platforms has radically changed the system of information production and dissemination. Information that was once the product of a small group of people turned into a product produced by the masses. Anyone can make and disseminate information. This condition is a positive indicator for democracy. However, this phenomenon creates space for the emergence of complex challenges. The democratization of information that is close to liberalization has an impact in the form of a mixture of facts and opinions, between truth and hoaxes. Without adequate critical thinking skills, one will only become the object of the democratization of information. In response to these conditions, this study aims to equip new students within the Faculty of Social and Political Sciences UPNVJ with critical thinking skills that include theoretical to practical aspects. The training method uses an interactive material delivery model, case studies, and group discussions. The results of the training showed a significant increase in understanding, application skills, and awareness of the importance of critical thinking in assessing information and solving social issues. This activity is expected to be the first step of intervention and mentoring for new students who are starting to enter the academic world and are open to the process of digitizing information.